The legal lawyers’s offices and the popularization of the right - SANDRA PATRICIA DUQUE QUINTERO; ELVIA MARIA GONZALEZ AGUDELO (Prisma Jurídico, 2008)
This research paper develops the concept of popularization of science and how it should be articulated in a multidisciplinary and interdisciplinary context. The relationship of science with the environment, the need to trace the popularization and ask about its scope and how the interior of the university can potentiate these processes of dissemination of knowledge in all areas of acquaintance, in which the law as a leading social science should not be absent. In this sense reflects the clinical legal education as a curriculum in the training of lawyers that would popularize the law and teaching as a theoretical and practical tool to enable this process.